iMMAS an Industrial Meta-Model for Automation System Using OPC UA - Miguel Gutierrez-Guerrero, Jose; Antonio Holgado-Terriza, Juan (Elektronika ir Elektrotechnika, 2017)
Industry 4.0 promotes the integration of IT software technology with the industrial devices of a factory for the supervision and control of Industrial Automation Systems (IAS). In this paper, a novel metamodel called iMMAS (Industrial Meta-Model for Automation System) is proposed to simplify the development and deployment of an IAS. The metamodel provides a language for modelling the industrial process of a factory through industrial devices (including PLC, Soft-PLC or RTU) using new abstractions to conceptualize the IAS. This work presents how the models are performed and executed on an OPC UA environment, and how they can be used to generate a program for a PLC. A case study is also shown to test the applicability of the proposal presented. DOI: http://dx.doi.org/10.5755/j01.eie.23.3.18324